2017
DOI: 10.21037/jtd.2017.06.90
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after implementing the enhanced recovery after surgery protocol for patients undergoing tuberculous empyema operations

Abstract: Background: Enhanced recovery after surgery (ERAS) protocols provide recommendations for care in various surgical fields. However, there is scarce information on the application of these protocols in tuberculous empyema surgery. The purpose of this research is to evaluate the outcomes of ERAS recommendations for patients who received tuberculous empyema surgery. Methods: A retrospective analysis was performed on patients who underwent tuberculous empyema surgery in our hospital from March 2011 to March 2016. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…A retrospective analysis by Xia and colleagues 12 of 92 patients undergoing surgery for tubercular empyema, included 45 patients in the ERAS group and 47 in the conventional treatment group. They concluded that the ERAS group had a shorter chest tube duration, less chest tube drainage, and a shorter length of stay compared to the conventional group.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis by Xia and colleagues 12 of 92 patients undergoing surgery for tubercular empyema, included 45 patients in the ERAS group and 47 in the conventional treatment group. They concluded that the ERAS group had a shorter chest tube duration, less chest tube drainage, and a shorter length of stay compared to the conventional group.…”
Section: Discussionmentioning
confidence: 99%
“…Atualmente, a combinação de tratamento medicamentoso anti-infeccioso e toracostomia/ toracocentese intermitente sempre mostra efeito terapêutico em pacientes com envolvimento pulmonar, pleural, mediastinal ou da parede torácica, podendo promover a resolução completa da pleura parietal visceral espessada e manter a capacidade funcional do pulmão em grande medida. (6)(7)(8) No presente estudo, o RR-CTE foi comum em todas as idades, fato corroborado por Somenath Kundu e Acharya et al (9,10) A cirurgia limparia a lesão intratorácica e permitiria a excisão da placa de fibra. Além disso, a elasticidade normal do tórax seria restaurada, a função pulmonar seria melhorada e a duração do tratamento seria encurtada.…”
Section: Carta Ao Editorunclassified